Tape: an alternative to stirrups or wedges in positioning for infant cystoscopy. Issue 3 (June 2020) - Martin, Benjamin; Chandran, Harish
Summary: Performing a cystourethroscopy in children can range from reviewing a 100 kg teenage male with posterior urethritis, to assessing a 3 kg neonate with posterior urethral valves. Across this range the patient needs to be positioned in a way that allows passage of the rigid cystoscope and visualisation of the urethra and bladder. We describe a technique for positioning the legs of infants for cystoscopy using skin friendly tape, rather than wedges, stirrups or boots. The advantage of this being that it is cheap, adaptable and holds the infant in the perfect position, without needing complex equipment.